2002
DOI: 10.1520/jfs15565j
|View full text |Cite
|
Sign up to set email alerts
|

Utilized Coefficient of Friction During Walking: Static Estimates Exceed Measured Values

Abstract: This study compared utilized coefficient of friction (COF) measured during nonslip pedestrian gait to estimated utilized COF values calculated using anthropometric (i.e., leg length) and stride characteristic data (i.e., impact angle, step length). Twenty healthy adults walked at slow, medium, and fast speeds with kinematic and kinetic data recorded simultaneously. Estimated and measured impact angle varied with walking speed, with greater angles evident with faster speeds (p < 0.001 and p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
3
26
2
Order By: Relevance
“…Thus the pigs reduced their peak uCOF by 33% from dry to greasy condition and from dry to wet condition by 12%, which was very similar to the reduction in the uCOF produced by humans anticipating slippery floors (Cham and Redfern, 2002). Part of the explanation for the reduced peak uCOF was the pigs' lowered speed when walking on contaminated floors, which was supported by the finding of others that the uCOF is positively correlated with walking speed (Powers et al, 2002). In cows, the uCOF was 0.54 when walking straight and 0.83 in single cases of a cow walking a curved path (Van der Tol et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Thus the pigs reduced their peak uCOF by 33% from dry to greasy condition and from dry to wet condition by 12%, which was very similar to the reduction in the uCOF produced by humans anticipating slippery floors (Cham and Redfern, 2002). Part of the explanation for the reduced peak uCOF was the pigs' lowered speed when walking on contaminated floors, which was supported by the finding of others that the uCOF is positively correlated with walking speed (Powers et al, 2002). In cows, the uCOF was 0.54 when walking straight and 0.83 in single cases of a cow walking a curved path (Van der Tol et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…The value of 10% was chosen to avoid the very early and late stance phase parts during which spurious maxima occur due to division by small values of vertical forces (Powers et al, 2002). Furthermore, the boundary ensured that at least 5% of the body weight was on the limb, corresponding to the definition by Hanson et al (1999).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…These originated from small vertical force values during claw-on and claw-off. Because of division by small numbers in the UCOF ratio, these UCOF values showed false maxima (Cham & Redfern, 2002;Powers et al, 2002). …”
Section: Data Processingmentioning
confidence: 99%
“…A sufficient COF value for standing and locomotion is suggested to be at least 0.35-0.40 (Webb & Nilsson, 1983). Cham & Redfern (2002) found that a human subject used both postural and temporal gait adaptions to reduce the risk of slipping when anticipating slippery floor conditions, while according to Powers et al (2002), the peak UCOF increases with increasing walking speed. In order to understand the relationship between floor properties and claw disorders in cows, slip direction and magnitude (Albutt et al, 1990), gait pattern on dry and slurry-covered floors (Phillips & Morris, 2000;Telezhenko & Bergsten, 2005), and how UCOF values differ during different locomotion situations (van der Tol et al, 2005) have been investigated.…”
Section: Introductionmentioning
confidence: 99%